Evaluation of patient factors for surgical site infection in Elective Ear, Nose, Throat and Head-Neck Surgery (Bangladesh Journal of Otorhinolaryngology, 2024)
Background: Surgical site infection (SSI) is one of the most common health care associated infection and still among the most common serious complications of surgery and have serious consequences for outcomes and costs. Different patient factors may be involved for SSI, including advanced age, diabetes, smoking, alcoholism, steroid/ immunosuppressive medication, poor nutritional state, obesity, anemia, jaundice, chronic infectious disease and malignancy. SSI previously called postoperative wound infection, results from bacterial contamination during or after a surgical procedure. SSI are incisional (superficial or deep) and organ space infection. A successful outcome after ENT and Head-Neck surgery is highly dependent on the postoperative complications. There is little information regarding patient factors for surgical site infection in elective ear, nose, throat and head-neck surgery.Objectives: The aim of our study was to identify risk factors for developing Surgical Site Infections (SSI) among patients having Ear, Nose, Throat (ENT) and Head-Neck surgery. Materials & method: This prospective type of observational study was conducted in ENT and Head-Neck surgery departments of Dhaka Medical College Hospital, Dhaka, during the period of March, 2018 to September, 2018. A total 250 patients were selected after they have enrolled for elective operation in ENT and Head-Neck surgery department. All relevant data was collected from patients’ history, clinical examination, investigations and hospital records and those was recorded in prescribed form (Data collection sheet). After preoperative preparation specific operation was done. All patients were followed up for development of any postoperative wound infection. All information recorded in data collection sheet. Data was processed and analysed with the help of computer program SPSS and Microsoft excel. Quantitative data expressed as mean and standard deviation and qualitative data as frequency and percentage. Result: Mean age of the participants was 32.79 (SD ±18.96) years. Among 250 patients, 7(2.8%) patients developed postoperative SSI. SSI is significantly higher in older age group (p value